Vein of Galen aneurysmal malformation in newborns: a retrospective study to describe a paradigm of treatment and identify risk factors of adverse outcome in a referral center - Buratti, Silvia; Mallamaci, Marisa; Tuo, Giulia; Severino, Mariasavina; Tortora, Domenico; Parodi, Costanza; Rossi, Andrea; Pasetti, Francesco; Castellan, Lucio; Capra, Valeria; Romano, Ferruccio; De Marco, Patrizia; et al. (Frontiers in Pediatrics, 2023)
Background: Vein of Galen aneurysmal malformation (VGAM) is a rare cerebral vascular malformation associated with significant morbidity and mortality. Newborns with VGAM without adequate treatment may develop rapidly deteriorating high output heart failure (HOHF) and are at risk for severe neurological outcomes. Objective: To describe the clinical course and management of newborns with VGAM, and identify which echocardiographic and neuroradiologic factors may be associated with severe heart failure at birth and adverse short term outcomes. Methods: This is a single center retrospective cohort study including all consecutive newborns with VGAM admitted to Gaslini Children’s Hospital between 2009 and 2022. We reviewed clinical data, intensive care support, fetal and neonatal cardiologic and neuroradiologic findings and we studied the association with severe HOHF, endovascular complications and death. Results: Out of 40 newborns, 17 (42.5%) developed severe HOHF requiring early endovascular procedures. Medical treatment was focused on the main components of HOHF by providing inotropic support and peripheral vasodilation. Pulmonary vasodilators were avoided to reduce the negative effects of pulmonary overflow and prevent vascular remodeling. Reduction of the obligatory left to right shunt through the VGAM was possible only through endovascular treatment. Fetal cardiothoracic ratio was significantly associated with severe HOHF at birth and death. Cardiologic parameters of right ventricular overload, pulmonary hypertension and systemic steal were the leading findings associated with haemodynamic compromise at birth. The mediolateral diameter of the straight or falcine sinus at its shortest section (SS-MD), and arterial pseudofeeders were significantly associated with severe HOHF at birth in prenatal and postnatal assessments. None of the postnatal echocardiographic and MRI variables, nor a higher inotropic support were associated with major periprocedural complications or death. Mortality was due to palliation for congenital severe brain damage (4/40, 10%), or major periprocedural complications (3/40, 7.5%). None of the patients died due to HOHF and multiorgan failure. Overall survival at discharge was 82.5% (33/40). Conclusions: The complexity of neonatal VGAM pathophysiology requires a multidisciplinary approach, specialized intensive care management, and early endovascular treatment to reduce mortality and optimize clinical outcomes. Cardiologic and neuroradiologic parameters are key to define risk stratification and treatment strategies.